2022
DOI: 10.1155/2022/9959044
|View full text |Cite
|
Sign up to set email alerts
|

Adult Hippocampal Neurogenesis in Alzheimer’s Disease: An Overview of Human and Animal Studies with Implications for Therapeutic Perspectives Aimed at Memory Recovery

Abstract: The mammalian hippocampal dentate gyrus is a niche for adult neurogenesis from neural stem cells. Newborn neurons integrate into existing neuronal networks, where they play a key role in hippocampal functions, including learning and memory. In the ageing brain, neurogenic capability progressively declines while in parallel increases the risk for developing Alzheimer’s disease (AD), the main neurodegenerative disorder associated with memory loss. Numerous studies have investigated whether impaired adult neuroge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 141 publications
0
9
0
Order By: Relevance
“…We currently do not know the full mechanisms(s) by which AHN is impaired in AD, which should be complex and diverse. Mounting evidence from in vivo and in vitro studies showed the presence and levels of Aβ and pTau contribute to AHN impairment in AD (for review, (Culig et al, 2022; Farioli‐Vecchioli et al, 2022; Liu et al, 2021); the references cited in the review papers). Moreno‐Jiménez et al indeed found that the number and maturation of adult‐born neurons declined progressively with the advancement of Braak stages in AD patients (Moreno‐Jiménez et al, 2019).…”
Section: The Mechanisms Of Ahn Impairment In Admentioning
confidence: 99%
“…We currently do not know the full mechanisms(s) by which AHN is impaired in AD, which should be complex and diverse. Mounting evidence from in vivo and in vitro studies showed the presence and levels of Aβ and pTau contribute to AHN impairment in AD (for review, (Culig et al, 2022; Farioli‐Vecchioli et al, 2022; Liu et al, 2021); the references cited in the review papers). Moreno‐Jiménez et al indeed found that the number and maturation of adult‐born neurons declined progressively with the advancement of Braak stages in AD patients (Moreno‐Jiménez et al, 2019).…”
Section: The Mechanisms Of Ahn Impairment In Admentioning
confidence: 99%
“…One possible mechanism through which tau can impact on adult hippocampal neurogenesis could be through its accumulation in the hyperphosphorylated form in GABAergic interneurons of the DG in both AD patients and in the 3xTg-AD transgenic mouse model of AD [ 63 ]. Consequently, the reduction of GABA and the disinhibition of local circuits and astrogliosis could in turn impair adult hippocampal neurogenesis [ 64 ].…”
Section: Ethiopathogenesis Of Admentioning
confidence: 99%
“…Adult hippocampal neurogenesis has several potential functions such as increasing resilience against stress, enhancing pattern separation [ 89 ], the formation of memory and learning [ 90 , 91 ] and inducing the loss of established or old memories [ 92 ]. Indeed, AD mouse model studies have shown that altered neurogenesis was linked to deficits in pattern integration, pattern separation, and cognitive flexibility [ 64 ]. In a study conducted by Nakashiba et al, it was reported that older neurons are mainly implicated in pattern completion as they recognize relatively distinct situations, while younger neurons are essential for the fine discrimination of close contexts.…”
Section: Ethiopathogenesis Of Admentioning
confidence: 99%
See 1 more Smart Citation
“…The process of neurogenesis is influenced by pathologies, such as stroke and other brain lesions, psychiatric diseases or epileptic seizures [19,[22][23][24][25]. In particular, after an experimental stroke, there is an increase in neurogenesis, as reflected by enhanced proliferation and differentiation of stem cells, which depends on the size of the infarcts [26][27][28].…”
Section: Introductionmentioning
confidence: 99%